Father support is protective against the negative effects of perceived discrimination on CRP among sexual minorities but not heterosexuals. (December 2019) - Wood, Erica P.; Cook, Stephanie H.
Highlights: Father support moderated the association between perceived discrimination and CRP among sexual minorities (SMs). Mother support did not moderate the association between perceived discrimination and CRP among heterosexuals or SMs. Father support may protect against the effects of perceived discrimination on indices of cardiovascular risk among SMs. Abstract: Background: Exposure to sexual orientation-related discrimination among sexual minorities may lead to elevated levels of C-reactive protein (CRP) as compared to their heterosexual counterparts. However, little is known about factors that may buffer the association between discrimination and CRP among sexual minorities versus heterosexuals. The current study examined if the association between discrimination, sexual orientation, and CRP differed across levels of social support from one's father/father-figure or mother/mother-figure between sexual minorities and heterosexuals. Methods: Data came from Wave IV of the National Longitudinal Study of Adolescent to Adult Health (Add Health). The sample sizes for father support and mother support was 3167 and 3575, respectively. Participants ranged in age from 24 to 33 years. Stratified linear regression models examined if father and mother support moderated the association between discrimination and CRP among sexual minorities and heterosexuals. Results: Father support significantly moderated the association between discrimination and CRP among sexual minorities but not heterosexuals. Sexual minorities with higher father support and who experienced discrimination had lower CRP as compared to those with lower father support and who experienced discrimination. Mother support did not moderate the association between discrimination and CRP among either sexual minorities or heterosexuals. Conclusion: Father support may mitigate the negative effects of stress from discrimination on CRP among sexual minorities. Future research should further examine the potential differential role that father support may play in reducing cardiovascular risk among sexual minorities versus heterosexuals who experience discrimination.